Identification and Determination of Dimensions of Health-Related Quality of Life for Cancer Patients in Routine Care – A Qualitative Study - Schrage, Theresa; Görlach, Mirja; Schulz, Holger; Bleich, Christiane (Frontiers in Psychology, 2022)
Purpose Continuous patient-reported outcomes (PROs) to identify and address patients’ needs represent an important addition to current routine care. The aim of this study was to identify and determine important dimensions of health-related quality of life (HrQoL) in routine oncological care. Methods In a cross-sectional qualitative study, interviews and focus groups were carried out and recorded. The interviewees were asked for their evaluation on HrQoL in general and specifically regarding cancer treatment. The material was transcribed and analyzed using qualitative content analysis based on Mayring. The results were reviewed in an expert discussion. Results Interviews with patients (N = 28) and clinicians (N = 4), as well as five focus groups with clinicians (N = 18) were conducted. Initially, nine deductive and two inductive categories on HrQoL were built. Four categories (partnership/sexuality, spirituality/religiousness, health perception, and overall health) were excluded following the qualitative content analysis because they were hardly or not at all mentioned by participants. Following on from the analysis of the expert discussion, one dimension was added (dignity), and two further categories were excluded (mobility and feeling of security in treatment). The resulting system consisted of six dimensions: emotional health, physical ailments, autonomy, social functionality, dignity, and resources. Conclusion The identified dimensions of HrQoL in routine oncological care were found to differ from those used in existing HrQoL measurements for (cancer) patients. Further research is needed to test and evaluate the presented structure in a larger sample of cancer patients to further assess its psychometric properties.